The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1108/nfs-12-2018-0334
|View full text |Cite
|
Sign up to set email alerts
|

Functional goat meat nuggets fortified with novel bioactive Carica papaya L. and Origanum vulgare extracts and storage stability thereof

Abstract: Purpose This paper aims to highlight the candidature of papaya/Carica papaya L. extracts (PLE) and oregano/Origanum vulgare leaves extract (OLE) as novel natural antioxidants, which was further fortified into goat meat nuggets to evaluate quality changes and storage stability at refrigeration temperature (4 ± 1ºC) for 20 days. Design/methodology/approach Three different products, namely, control (without phyto-extracts), T−1: PLE (0.5 per cent) and T-2: OLE (1.0 per cent) fortified goat meat nuggets, were pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…The addition of 5% citrus extracts (orange and lemon) completely inhibited the growth of lactic acid bacteria in beef meatballs over 12 days of refrigerated storage (Fernandez-Lopez et al , 2005). Similarly, Jagtap et al (2020) observed extension in shelf life of goat meat nuggets by using papaya and oregano leaves extracts under refrigerated storage.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…The addition of 5% citrus extracts (orange and lemon) completely inhibited the growth of lactic acid bacteria in beef meatballs over 12 days of refrigerated storage (Fernandez-Lopez et al , 2005). Similarly, Jagtap et al (2020) observed extension in shelf life of goat meat nuggets by using papaya and oregano leaves extracts under refrigerated storage.…”
Section: Resultsmentioning
confidence: 85%
“…Similarly, Hasani and Javadian (2016) reported significantly ( p < 0.05) lower TBARSs values in common carp fillets treated with orange peel extract and BHT than the control samples during the refrigerated storage. Jagtap et al (2020) observed the oxidative stability in goat meat nuggets incorporated with papaya and oregano leaves extract. The results of the present study indicate that orange peel and moringa leaves extracts delivered similar lipid oxidation inhibition.…”
Section: Resultsmentioning
confidence: 96%
“…In the last years, several studies using sheep and goat meats with cooked or precooked products and some products ready to cook have been developed as patties [44][45][46][47], nuggets [48][49][50][51][52][53][54], hamburgers [55,56] or pâté [11,[57][58][59] and others [60][61][62][63]. In the Indian subcontinent (India, Pakistan, Bangladesh, Nepal and Sri Lanka), there are several traditional meat products and recipes using sheep and goat meats, such as Rogan Josh, a lamb meat marinated with Kashmiri chilies, Aab Gosht, a lamb curry cooked in milk, Rista and Goshtaba, a minced lamb meat cooked in mutton stock gravy, Haleem prepared from goat or buffalo meats or Kolhapuri mutton with different curries [64].…”
Section: Cooked or Precooked Prepared Productsmentioning
confidence: 99%
“…Buffalo meat contains high biological value protein and micronutrients and is considered as the healthiest meat among red meat known for human consumption (Goswami et al, 2018).The buffalo veal, an unexplored meat type, was used for the development of ground meat slices to assess its product acceptability. A comparison of developed slices with respect to goat meat (chevon), the most popular red meat in the country consumed by all the segments of the society (Jagtap et al, 2019a), produced a better picture regarding the product quality and its acceptability in addition to the explorative study on buffalo veal.…”
Section: Introductionmentioning
confidence: 99%